Resting cells isobutanol production by Shimwellia blattae (p424IbPSO): Influence of growth culture conditions. (3rd October 2018) - Acedos, Miguel G.; Santos, Victoria E.; Garcia‐Ochoa, Felix
Abstract : Isobutanol is a promising gasoline additive and could even be a potential substitute used directly as combustible. In this work, the production of isobutanol from glucose by Shimwellia blattae (p424IbPSO) in resting cell cultures is studied. This production has two stages, involving a resting cell phase that has not been studied before. The cell growth was carried out under different operating conditions: temperature and medium composition (YE, ammonium, and IPTG concentrations), looking for the highest isobutanol production. Moreover, the cells were collected at three different growth times checking their isobutanol production capacity. The best operating conditions have been determined as: 30°C of temperature, a medium containing 1.5 g L −1 YE and 1.4 g L −1 of ammonium as nitrogen sources, adding 0.5 mM IPTG as inducer. The cells collected at early growth times are significantly more active. The use of S. blattae (p424IbPSO) in resting cells is a good strategy for the production of isobutanol from glucose yielding better results than in batch growth cultures, a yield of 60% attainment of theoretical maximum yield is obtained under optimal conditions. In addition, it has been demonstrated that if the cells are cultured at higher temperatures and with high IPTG concentrations, inclusion bodies are formed in the cytoplasm inhibiting the isobutanol production in the resting cell stage.